Electron Microscopy Characterization of Electrodeposited Homogeneous and Multilayered Nanowires in the Ni-Co-Cu System. Issue 11 (1st January 2018) - Zsurzsa, S.; Pellicer, E.; Sort, J.; Péter, L.; Bakonyi, I.
Abstract : Homogeneous and multilayered nanowires in the Ni-Co-Cu system were fabricated by template-assisted electrodeposition in anodized aluminum oxide membranes from an aqueous electrolyte under potentiostatic control. By using d.c.-plating, homogeneous Ni-Co-Cu nanowires were fabricated for which the optimum deposition potential ensuring uniform pore filling was established. A multilayered magnetic/non-magnetic Ni-Co/Cu nanowire structure was achieved during growth along the length of the nanowires by employing two-pulse plating. Here, the optimum deposition potential of the magnetic layer for uniform pore filling was found to be the same as established before for the homogeneous nanowires. For the non-magnetic layer deposition potential, we have selected the optimum value determined in our previous works on multilayer films, which ensures that neither a dissolution of the magnetic layer can occur during the Cu layer deposition, nor magnetic atoms are codeposited into the non-magnetic layer; this feature is a novelty for the electrodeposition of multilayered nanowires. For the multilayered nanowires, the electrodeposition parameters were set to obtain equal thicknesses of both kinds of layer with a repetition period of 10 nm. Structural and compositional characterization of the nanowires was carried out using various electron microscopy imaging, diffraction and spectroscopy techniques which confirmed the multilayered structure of the nanowires with the intended individual layer thicknesses. These results demonstrate that, by using an optimized Cu deposition potential, we could successfully produce nanowires with well-defined layered structures for individual and bilayer thicknesses smaller than usually reported.